Hierarchical ultrathin alumina membrane for the fabrication of unique nanodot arrays. (2nd December 2015) - Wang, Yuyang; Wang, Yi; Wang, Hailong; Wang, Xinnan; Cong, Ming; Xu, Weiqing; Xu, Shuping
Abstract: Ultrathin alumina membranes (UTAMs) as evaporation masks have been a powerful tool for the fabrication of high-density nanodot arrays and have received much attention in magnetic memory devices, photovoltaics, and nanoplasmonics. In this paper, we report the fabrication of a hierarchical ultrathin alumina membrane (HUTAM) with highly ordered submicro/nanoscale channels and its application as an evaporation mask for the realization of unique non-hexagonal nanodot arrays dependent on the geometrical features of the HUTAM. This is the first report of a UTAM with a hierarchical geometry, breaking the stereotype that only limited sets of nanopatterns can be realized using the UTAM method (with typical inter-pore distance of 100 nm). The fabrication of a HUTAM is discussed in detail. An improved, longer wet etching time than previously reported is found to effectively remove the barrier layer and widen the pores of a HUTAM. A growth sustainability issue brought about by pre-patterning is discussed. Spectral comparison was made to distinguish the UTAM nanodots and HUTAM nanodots. Our results can be an inspiration for more sophisticated applications of pre-patterned anodized aluminum oxide in photocatalysis, photovoltaics, and nanoplasmonics.